Sacred Texts and Magical Realism: Intertextual Strategies in Feby Indirani’s Bukan Perawan Maria - Prawira, Mentari Putrirahayu; Nabila, Atika Silma; Hermawan, Muhammad Alfian; Effendi, Anwar; Maslihatin, Anis (Makassar State University, 2026)
This study examines the use of intertextuality in Feby Indirani’s magical realism short stories. The research aims to explore how intertextual references to religious texts, cultural narratives, and literary traditions function as narrative strategies within the framework of magical realism. The present study adopts a qualitative descriptive approach, focusing on close reading of three short stories in the collection to identify intertextual elements and their integration into the magical realist mode. The analysis considers how these intertextual layers create a narrative space where supernatural elements are treated as natural parts of reality, enabling a subtle critique of patriarchal and religious norms. The findings indicate that intertextuality plays a central role in shaping the work's magical realist texture, providing depth and resonance through layered cultural references. This strategy not only enriches the text's aesthetic dimension but also strengthens its capacity for social commentary. The study contributes to the understanding of how contemporary Indonesian literature employs intertextuality to construct magical realism as a means of negotiating cultural identity and challenging dominant social discourses. This study also contributes to Indonesian literary scholarship by demonstrating how intertextuality and magical realism operate as mutually reinforcing narrative strategies in progressive Islamic literature